Hubungan Antara Derajat Merokok Aktif, Ringan, Sedang Dan Berat Dengan Kadar Saturasi Oksigen Dalam Darah (SpO2) - Wahyu Tri Sudaryanto (Interest : Jurnal Ilmu Kesehatan, 2017)
Abstract: Degree Of Smoking, Oxygen Saturation, Cigarettes. Smoking is tobacco smoke inhalation activity detrimental to the health of the body that is addictive. Category degrees smoking in Brinkman index is divided into three types of categories: mild, moderate and severe. The more severe the degree of smoke someone then the higher the harmful substances that are inhaled by the body and will affect the value of the oxygen saturation in the blood. This study aimed to petition was to determine the relationship of the degree of smoking with oxygen saturation levels in the blood. The study was an observational study with a cross-sectional design. The sample in this study amounted to 90 people were taken through purposive sampling method, measurement in research using measuring devices such as Brinkman index to measure the degree of smoking while using oxygen saturation value measurement tools oximetry measuring pulse. From the results of the test to get the correlative Somers'd p <0.05 on the relationship between the degree of smoking with oxygen saturation values. There is a relationship between the degree of smoking with oxygen saturation levels in the blood.